Global governance and climate stress of incarcerated women: the case of the U.S - Jauk-Ajamie, Daniela (International journal of comparative and applied criminal justice, 2023)
This paper takes the United States as a case study on the gendered implications of hyper-incarceration in the age of climate emergency. Prisons here are often located on toxic sites and constitute sources of contamination; climate change and global warming exacerbate these conditions. Incarcerated women and their communities are particularly affected. The female incarceration rate has skyrocketed, and women come to the carceral complex with unique histories of abuse, and higher rates of physical and mental illness. Researchers and policymakers need to address, analyse, and include incarcerated women’s experiences of climate stress in global policy mechanisms such as the UN Commission on the Status of Women (CSW) and the United Nations Rules for the Treatment of Women Prisoners and Non-custodial Measures for Women Offenders (“Bangkok Rules”). Abolition feminism and the voices of incarcerated women should meaningfully help connect the dots in the larger framework of the Sustainable Development Goals (SDGs).